PEM fuel cell failure mode analysis - Wang, Haijiang Henry; Li, Hui, 1964-.; Yuan, Xiao-Zi (Boca Raton : Taylor & Francis, 2012)
'PEM Fuel Cell Failure Mode Analysis presents a systematic analysis of PEM fuel cell durability and failure modes. It provides readers with a fundamental understanding of insufficient fuel cell durability, identification of failure modes and failure mechanisms of PEM fuel cells, fuel cell component degradation testing, and mitigation strategies against degradation. The first several chapters of the book examine the degradation of various fuel cell components, including degradation mechanisms, the effects of operating conditions, mitigation strategies, and testing protocols. The book then discusses the effects of different contamination sources on the degradation of fuel cell components and explores the relationship between external environment and the degradation of fuel cell components and systems. It also reviews the correlation between operational mode, such as start-up and shut-down, and the degradation of fuel cell components and systems. The last chapter explains how the design of fuel cell hardware relates to failure modes.'--Publisher's description.
Introduction -- Catalyst degradation -- Catalyst support degradation -- Membrane degradation -- Porous transport layer degradation -- Degradation of bipolar plates and its effect on PEM fuel cells -- Degradation of other components -- Contaminant-induced degradation -- Environment-induced degradation -- Operation-induced degradation -- Design-related durability issues.
Includes bibliographical references and index.
Keywords: Proton exchange membrane fuel cells -- Reliability; Proton exchange membrane fuel cells -- Testing; System failures (Engineering)